(untitled) (Costos y Gestión, 2021)
This work proposes a model of indicators related to higher education to be used in the management process of institutions dedicated to this level of training. It is about the adaptation of an extract of the work delivered in the development of the module «Management of Educational Entities» of the postgraduate career «Specialization in Costs and Business Management», dictated at the Faculty of Economic Sciences and Statistics of the National University of Rosario, Argentina, as a requirement of approval, in December 2016. The study is based on a previous analysis, the authors of which are cited opportunely, in an attempt to provide additional respectful contribution to broaden the vision of those who use this tool in the management of entities educational. The reason for its presentation, in addition to its undoubted utility for users, is to disseminate the material that arises as an elaboration of the students, who, in addition to absorbing knowledge transferred by the teacher, in a traditional way of learning, also carry out a own construction of knowledge, within the theoretical framework and with the search for information.